Q-OPERATÖRÜ VE STURM-LİOUVİLLE PROBLEMİ - AŞUT, SARİYE (Fırat Üniveristesi, 2017)
Bu tez üç bölümden oluşmaktadır. Birinci bölümde, q-fark operatörleri ile ilgili genel bir tarihçe verilmiştir. İkinci bölümde, q-fark operatörü, q-fonksiyonlar ve q-fonksiyonlar uzaylarının özellikleri incelenmiştir. Konuyla ilgili temel tan¬m ve teoremler verilmiştir. Üçüncü bölümde, L 2 q (0,a) Hilbert uzayında q-Sturm-Liouville Problemi verilmiştir. Bu problem ile ilgili genel spektral özellikler incelenmiştir. Ayrıca G(x,t,landa) Green fonksiyonunun özellikleri verilip bununla ilgili temel tan¬m ve teoremler ispatlarıyla birlikte detaylı olarak verilmiştir. Özfoksiyonlarının açılım formülleri incelenmiştir.

This thesis consists of three chapters. In the first chapter, a general history related to q-difference operators is given. In the second chapter, properties of q-difference operator, q-functions and q-functions spaces are analyzed. Basic deffinitions and theorems related to the subject are given. In the third chapter, q-Sturm-Liouville Problem in L 2 Square (0,a) Hilbert space is given. General spectral properties related to this problem are analyzed. Also, properties of G(x,t,landa) Green functions are given and basic de…nitions and theorems related to this subject is given with proofs in detailed. Finally, expansion formulas of eigenfunctions of this problem are investigated.
Q-operator and sturm liouville problem
Keywords: Matematik